2010
DOI: 10.1016/j.cgh.2009.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Gluten-Free Diet and Steroid Treatment Are Effective Therapy for Most Patients With Collagenous Sprue

Abstract: BACKGROUND & AIMS Collagenous sprue (CS) is characterized by the presence of a distinctive band of subepithelial collagen deposition in the small bowel. We evaluated the clinical characteristics, treatments, and outcomes of patients with CS. METHODS Thirty patients with CS were identified at the 3 Mayo Clinic sites between 1993 and 2009. Clinical data from medical records were reviewed. RESULTS The study cohort was 70% female (age range, 53–91 years). Most patients had severe diarrhea and weight loss. Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 38 publications
1
62
0
Order By: Relevance
“…To date, olmesartan-related enteropathy has been rarely reported in literature, mainly as single case reports (8,9), or associate findings during evaluation of cohorts of celiac (1) or collagenous sprue patients (10), and only a relatively consistent case series (including 22 subjects) has been published (7). Albeit infrequent, this enteropathy may be quite severe in more than 50 % of cases -to the point that it received a recent FDA warning (11)-, and it is often considered as unresponsive celiac disease (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, olmesartan-related enteropathy has been rarely reported in literature, mainly as single case reports (8,9), or associate findings during evaluation of cohorts of celiac (1) or collagenous sprue patients (10), and only a relatively consistent case series (including 22 subjects) has been published (7). Albeit infrequent, this enteropathy may be quite severe in more than 50 % of cases -to the point that it received a recent FDA warning (11)-, and it is often considered as unresponsive celiac disease (7).…”
Section: Discussionmentioning
confidence: 99%
“…Blood chemistry revealed hemoglobin 13 g/ dL (n.v. [13][14][15][16][17], serum potassium 2.3 mEq/L (n.v. 3.5-5-5), calcium 6 mg/dL (n.v. 8.5-10.7), magnesium 0.8 mg/ dL (n.v. 1.5-2.6), phosphorus 2.4 mg/dL (n.v. 2.5-5), albumin 2.9 g/dL (n.v. 3.5-5.5), prealbumin 15.5 mg/dL (n.v. 20-40), total protein 4.9 g/dL (n.v. 6.2-8.5), B12 vitamin 103 pg/mL (n.v. 180-914), folic acid 2.7 ng/mL (n.v. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Abdominal ultrasound scans revealed mildly dilated small bowel loops in the epigastric area, mild hepatomegaly with steatosis, and biliary sludge.…”
Section: Case Reportmentioning
confidence: 99%
“…Indeed, there is recent evidence that these patients may be successfully treated (7), and the vast majority of patients with collagenous sprue (that sometimes display associated celiac disease) may have relatively good clinical outcomes (8).…”
Section: Discussionmentioning
confidence: 99%
“…The pathological hallmark of collagenous sprue is a thickened subepithelial collagen band with villous atrophy detected on distal duodenal biopsy. There is evidence that most patients (63–70%) with collagenous sprue suffer with other autoimmune conditions2 3 and that this is 12-fold more likely than in coeliac disease 2. Many of the coexisting autoimmune diseases affecting these patients include various types of arthritis, for which patients often require non-steroidal anti-inflammatory drugs (NSAIDs).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the coexisting autoimmune diseases affecting these patients include various types of arthritis, for which patients often require non-steroidal anti-inflammatory drugs (NSAIDs). Interestingly, the largest case series of collagenous sprue in the literature to date reported that 30% of patients with this diagnosis were taking acetylsalicylic acid or NSAIDs 3. It is therefore important to highlight the putative link between the latter medications and collagenous enteropathies,4 5 since NSAID cessation may potentially reverse collagen deposition.…”
Section: Introductionmentioning
confidence: 99%